2011
DOI: 10.1088/2040-8978/13/7/075402
|View full text |Cite
|
Sign up to set email alerts
|

A simple ultrasensitive displacement sensor based on a high bend loss single-mode fibre and a ratiometric measurement system

Abstract: An all-fibre displacement sensor with a simple configuration and capable of monitoring sub-50 nm displacements is proposed and investigated experimentally. The proposed fibre displacement sensor consists of a half-loop structure of bare high bend loss single-mode fibre 1060XP and a ratiometric power interrogation system. By measuring the change in transmission ratio in the ratiometric system, a change in displacement can be measured. The displacement sensor is sensitive to temperature and an experimental inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…It is well known that temperature variations affect the performance of any optical fiber sensor [ 12 ]. When temperature changes there are thermo-optic and thermal expansion effects that may modify the power transmission characteristics which may manifest as an undesirable attenuation in the whole spectral range or the wavelength shift of a given spectral notch.…”
Section: Intensity Based Displacement Sensormentioning
confidence: 99%
See 3 more Smart Citations
“…It is well known that temperature variations affect the performance of any optical fiber sensor [ 12 ]. When temperature changes there are thermo-optic and thermal expansion effects that may modify the power transmission characteristics which may manifest as an undesirable attenuation in the whole spectral range or the wavelength shift of a given spectral notch.…”
Section: Intensity Based Displacement Sensormentioning
confidence: 99%
“…This observation coincides with a measurement made by using a white light source, where we observed that at a given position the increase of temperature from 25 °C to 36 °C resulted in ∼0.1 dB loss. A more accurate measurement will require the use of a setup where the optical power source variations are compensated such as that proposed in reference [ 12 ].…”
Section: Intensity Based Displacement Sensormentioning
confidence: 99%
See 2 more Smart Citations
“…Optical fiber sensor, by virtue of its passive operation and immunity to electro-magnetic interference, opens up plentiful opportunities for displacement sensing applications in hard-to-reach circumstances. From the intuitive bending induced attenuation [1] to the sophisticated but highly sensitive fiber birefringence based interferometer [2], displacement information can be interrogated through the power change or the wavelength shift. Fiber Bragg grating (FBG), as one of the most widely used fiber sensor devices, also provides the displacement measurement solutions either by using an edge filter to interrogate the resonant wavelength [3] or a cantilever to transfer the displacement into the chirp profile of the FBG [4].…”
Section: Introductionmentioning
confidence: 99%